North America: corrected from the observations communicated to the Royal Society at London, and the Royal Academy at Paris. - Senex, John, d. 1740 (1710)
Map shows major settlements, areas of Native American habitation, and political divisions for the known extent of the continent of North America as far as the headwaters of the Mississippi River and the Great Lakes; Florida, Mexico, New Spain, islands of the West Indies, New Mexico, Greenland, New France, and New Britain; northwestern portions as "incognita," with a series of lakes and a "lake of salt," and lands of the nations of "Mozeemlecks" and "Gnacsitares." Relief shown pictorially. Scale not given.